The Death Euphemisms in Kazakh language and their sociocultural interpretation - Kiikshi, K.A.; Suleimenova, E.D. (KU Publ., 2021)
Talking about death has been a taboo subject in many societies and cultures, including the Kazakh culture. One of the most common ways to talk about death is through the use of euphemisms. The research aims to determine the most common euphemisms that Kazakh people use to describe death, and explore how their meanings reflect common socio-cultural beliefs about the notion of death. The descriptive survey model and the summative content analysis method are used to collect and analyse data. The connotations of the euphemisms are explored, and the Kazakh people’s cultural beliefs were interpreted and discussed in the context of the “death” euphemisms. As a result of the research, it is shown that the euphemisms that convey “death” used by Kazakh people correlate with their socio-cultural beliefs, often based on religion.
Қазақ тіліндегі «өлім» сөзіне эвфемизмдер жəне олардың əлеуметтік-мəдени тұрғыдан талдануы
Эвфемизмы к слову «смерть» в казахском языке и их социокультурная интерпретация
Keywords: euphemism; death; taboo; sociocultural beliefs; Kazakh people